2019
DOI: 10.1017/s0954579418001049
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effects of maternal love withdrawal and guilt induction on Chinese American preschoolers’ bullying aggressive behavior

Abstract: Bullying has been understudied among preschool children, especially those from Chinese American families. Previous research has also neglected the dimensional effects of psychological control on child bullying development. This study examined two psychological control dimensions, love withdrawal and guilt induction, and their effects on children's bullying aggressive behavior using a longitudinal design. Participants were first-generation Chinese American mothers (N = 133; mean age [Mage] = 37.82) and their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 66 publications
(101 reference statements)
5
62
1
Order By: Relevance
“…Research studies provided the evidence of highly significant effects of parenting interventions on bullying reduction . And some studies indicated that maternal love withdrawal prospectively predicted more aggressive bullying behaviors, whereas guilt induction predicted lower levels of aggressive bullying behaviors in children 6 months later (Yu et al, 2019). Therefore, bullying behaviors can be prevented by establishing a good parent-child relationship.…”
Section: Mediating Role Of Middle School Students' Lonelinessmentioning
confidence: 99%
“…Research studies provided the evidence of highly significant effects of parenting interventions on bullying reduction . And some studies indicated that maternal love withdrawal prospectively predicted more aggressive bullying behaviors, whereas guilt induction predicted lower levels of aggressive bullying behaviors in children 6 months later (Yu et al, 2019). Therefore, bullying behaviors can be prevented by establishing a good parent-child relationship.…”
Section: Mediating Role Of Middle School Students' Lonelinessmentioning
confidence: 99%
“…However, longitudinal research analysing parenting factors in pre-school and primary school children with Attention-deficit/ Hyperactivity Disorder (ADHD) or Oppositional Defiant Disorder (ODD) showed that higher levels of parental support for child autonomy were associated with a fall in the bullying rates among children over the five-year study (Rajendran, Kruszewski, & Halperin, 2016). Another longitudinal study found that maternal love withdrawal prospectively predicted more aggressive bullying behaviour, but child aggressive bullying behaviour did not predict love withdrawal (Yu, Cheah, Hart, Yang, & Olsen, 2019). Our study showed preliminary evidence of the association between parenting practices and bullying involvement (especially, for cyberbullying).…”
Section: Ineffective Parenting Practices (Poor Monitoring Inconsistent Discipline)mentioning
confidence: 99%
“…Parental love withdrawal centers on manipulating feelings of parental acceptance by the threat of or actual temporary withdrawal of love and attention (Barber, 1996; Mascolo, Fischer, & Li, 2003; Wu et al, 2002). We thus proposed that love withdrawal have negative connotations and implications for children's development whereas guilt induction and shaming may have more benign or even positive influences on Chinese children's development (Hoffman & Saltzstein, 1967; Rudy et al, 2014; Yu, Cheah, Hart, & Yang, 2018a; Yu, Cheah, Hart, Yang, & Olsen, 2018b, pp. 1–9).…”
Section: Subtypes Of Psychological Control and Cultural Contextmentioning
confidence: 99%